Anion receptors with nitrone C–H hydrogen bond donors. Issue 31 (29th March 2023) - He, Xuxian; Thompson, Richard R.; Clawson, Sarah A.; Fronczek, Frank R.; Lee, Semin
Abstract : We report the use of nitrone C–H groups as hydrogen bond donors for binding anions. Abstract : We report the use of nitrone C–H groups as hydrogen bond donors for binding anions. Acyclic anion receptors with two nitrone moieties were synthesized by condensation reactions between aryl-aldehydes and m -phenylenedihydroxylamines. The solid-state structure of dinitrones revealed C–H⋯O hydrogen bonds. Anion binding properties were investigated using NMR titration with halide and phosphate salts.